A Case of Pyriform Sinus Fistula with Respiratory Distress in the Neonatal Period - Noriko Hamaguchi; Hajime Ishinaga; Kazuki Chiyonobu; Hiroyuki Morishita; Kazuhiko Takeuchi (Case Reports in Otolaryngology)
Pyriform sinus fistula (PSF) is an anomaly that can arise due to failure of involution of the third or fourth branchial cleft during embryogenesis. It can manifest clinically as sinuses, cysts, or abscesses in the neck and is common in childhood. Herein, we describe a neonate who presented with neck swelling and respiratory distress, which was secondary to a fourth branchial pouch sinus. Physical examination revealed swollen areas in the posterolateral pharyngeal wall and on the external left side of the neck. Computed tomography imaging showed a left-sided mass that was filled with air and fluid. Eventually, the pyriform sinus cyst and the entire fistulous tract were excised. The postoperative course was uneventful. Follow-up after 18 months showed no recurrence.